STRUCTURAL EVIDENCE FOR COLLISION TECTONICS IN THE ARCHEAN OF EASTERN FINLAND - Jégouzo J.; Blais S. (My University, 1995)
Three main structural units are recognized in the Archean granito-gneissic basement of eastern Finland: (1) a lower unit (Kivijärvi orthogneisses), which is highly migma-tized and characterized by circular and elliptical structures with cores of anatectic granites; (2) a discontinuous middle unit composed of tectonic slices of mafic and ultramafïc rocks (associated with rare metasediments) that could represent fragments of ancient oceanic crust and (3) an upper unit (the Naavala orthogneisses) which is unmigmatized and has locally flat or gently dipping foliations. Structural mapping indicate that the middle unit is systematically located between the two main orthogneiss units. Shear criteria (shear bands, asymmetric pressure shadows) found in the middle and upper units indicate thrusting towards the west. The following model is proposed: (1) A western continental block (Kivijärvi gneisses) was separated by oceanic crust from an eastern crustal block (Naavala gneisses), (2) closure of the ocean was followed by continental thrusting from east to west and oceanic crust was preserved locally as tectonic slices, (3) subsequently, crustal thickening induced partial melting of the lower unit and this led to the diapiric emplacement of granites and (4) later, greenstone belt magmatism took place as the final Archean event. This model shows the existence, in Late Archean times, of tangential tectonic processes similar to those of more recent mountain belts.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей